Some Problems of Codification and Progressive Development of Humanitarian Law Applied to Non-international Armed Conflicts - N. V. Ostroukhov (Московский журнал международного права, 2009)
The article dwells on the issues of formation and development of the international legal norms regulating non-international armed conflicts.The author points out the stages of development of the norms under consideration and refers to the questions of recognizing nonintervention by a warring side and the International Red Cross Committee activities.The author studies the main points of the additional protocol tо the Geneva conventions, signed on August, 12th, 1949, that deals with the defense of the victims of armed non-international conflicts.